Pseudomyxoma peritonei due to mucinous adenocarcinoma of the appendix - S Idjuski; I Turkalj; K Petrovic; F M Vanhoenacker (Journal of the Belgian Society of Radiology, 2013)
A 60-year-old man was referred for evaluation of long-standing abdominal pain. CT scan of the abdomen showed a fluid-filled dilated appendix with mural calcifications (Fig. A, asterisk) and intraperitoneal low-attenuation mass like nodular formations (Fig. B, arrows) causing scalloping of liver contour (Fig. A, C, arrowheads). The patient underwent appendectomy and peritonectomy followed by uneventful postoperative recovery. Histopathological examination confirmed the radiological suspicion of pseudomyxoma peritonei (PMP) due to appendiceal mucinous adenocarcinoma.